Teaching skills for sustainable health care. Issue 1 (January 2023) - Stanford, Victoria; Barna, Stefi; Gupta, Dhruv; Mortimer, Frances
Summary: In the context of accelerating concern regarding the climate and ecological crisis and the recognition of this crisis as a health threat, there is growing motivation among the health-care community to reduce the negative environmental impact of health care. Globally, the health-care sector is estimated to be the 5th largest carbon emitter. A health system that is socially, environmentally, and financially sustainable requires clinical leadership, yet few health-care workers possess the conceptual framework or practical skills for creating new models of care. Clinicians can protect planetary health as a core part of professional practice by integrating triple bottom line measures into quality improvement or quality management practices. Initial efforts to integrate sustainability into quality improvement teaching and training have been shown to transform learners' interest in quality improvement and environmental sustainability. Embedding sustainability principles and techniques into established quality improvement education and practice can operationalise planetary health, building the skills necessary for health-care system transformation at the speed and scale required.